A security communication scheme for Real-Time EPON - Qu Jun-suo (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Problem of real-time performance is a mostly obstacle on Ethernet used to industrial control. In this paper, proposed a RT-EPON concept, combines real-time performance of real-time Ethernet and efficiency of EPON. And the security threats to the proposed architecture are analyzed. By utilizing the symmetric cryptographic techniques and challenge-response mechanism, a secure communication scheme with encryption and authentication functions is presented. DOI:http://dx.doi.org/10.11591/telkomnika.v10i5.1349